Programmable Ce6 Delivery via Cyclopamine Based Tumor Microenvironment Modulating Nano-System for Enhanced Photodynamic Therapy in Breast Cancer - Feng, Chan; Chen, Lv; Lu, Yonglin; Liu, Jie; Liang, Shujing; Lin, Yun; Li, Yongyong; Dong, Chunyan (Frontiers in Chemistry, 2019)
Photodynamic therapy (PDT) has shown great promise in breast cancer treatment. However, simplex target ligand modification or stimuli release cannot meet the requirement of effective drug delivery to solid tumor tissue. To overcome continuous bio-barriers existing in the tumor microenvironment, multi-stage response drug delivery was desirable. Herein, we developed a unique tumor microenvironment tailored nanoplatform for chlorin e6 (Ce6) delivery. We chose bovine serum albumin (BSA) as "mother ships" material for effective tumor periphery resident, cyclopamine (CYC) as extracellular matrix (ECM) inhibitor and synergistic anti-tumor agent, and diselenide containing amphiphilic hyaluronic acid-chlorin e6 polymers (HA-SeSe-Ce6) synthesized as “small bombs” for internal tissue destruction. The above three distinct function compositions were integrated into an independent CYC and HA-SeSe-Ce6 co-delivery albumin nano-system (ABN@HA-SeSe-Ce6/CYC). The obtained nano-system presents good biocompatible, long circulation and effective tumor accumulation. After entering tumor microenvironment, CYC gradually releases to disrupt the ECM barrier to open the way for further penetration of HA-SeSe-Ce6. Subsequently, targeted tumor cell internalization and intracellular redox response release of Ce6 would achieve. Moreover, CYC could also make up the deficiency of Ce6 in hypoxia area, owing to its anti-tumor effect. Improved therapeutic efficacy was verified in a breast cancer cell line and tumor-bearing mice model.